Peran Vital Generasi Muda Dalam Transformasi Pertanian Indonesia Ke Arah Masa Depan Yang Lebih Cerah: The Vital Role of the Young Generation in the Transformation of Indonesian Agriculture towards a Brighter Future - Fatinah, Intri Nur; Rozaki, Zuhud; Wulandari , Retno; Azzahra, Isni (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
This research details the crucial role played by Indonesia's young generation in driving the transformation of the agricultural sector towards a brighter future. In this context, the focus of the research lies on the significant contribution of the younger generation in integrating innovation, technology and sustainable approaches into the agricultural system. Through a collaborative approach, youth work with the government, research institutions and other stakeholders to initiate and implement innovative solutions that strengthen food security, increase productivity and reduce environmental impacts. An in-depth analysis of the role of the younger generation reveals that they are not only key actors in the adoption of modern technologies, but also agents of social change that drive agricultural sustainability. With the involvement of the younger generation, collaborative networks are formed that accelerate the transfer of knowledge and skills, expand access to resources, and stimulate the development of small-scale agricultural enterprises. Consequently, this transformation creates new economic opportunities, improves farmers' welfare and contributes to the achievement of sustainable development goals. The results of this research provide an in-depth look at how the vital role of the younger generation is a key pillar in creating a resilient, adaptive and highly competitive agricultural foundation. In conclusion, understanding and appreciating the contributions of the younger generation is not only relevant for agricultural transformation, but also crucial for building a sustainable and bright future for Indonesia.